PENGARUH PUPUK HAYATI KONSORSIUM MIKROBA DAN MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN TANAMAN JAGUNG PADA INCEPTISOL - Bahrotu Ilmi Nafiah; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Inceptisols are the main agricultural soils in Indonesia. However, Inceptisols have problems such as relatively low soil fertility, due to weathering and leaching. Increased fertilization efficiency can be achieved through the use of biological fertilizers, in the form of microbial consortium and arbuscular mycorrhiza. Maize plant can be used as an indicator of soil fertility because it is very responsive to nutrient treatments. The study aimed to determine the effect of microbial consortium and Arbuscular mycorrhizal (MA) biofertilizers on the growth of corn plants on Inceptisols. The application of microbial consortium and Arbuscular mycorrhizal (MA) biofertilizer was able to increased plant height at 6 WAP (Week After Planting) by 42% and 8 WAP by 34%, root length by 142%, number of spores by 216%, mycorrhizae colonies on the root by 60%, total population of bacteria by 248%, soil pH by 5,5%, available P by 29%, and C-organic by 49%. The effective dose of microbial consortium fertilizer to increase the growth of maize plants was 0.8 g polybag-1 (M2).